Manual de procedimientos para el cumplimiento de las obligaciones tributarias del sector comercial ferretero del cantón Macará, periodo 2023. - Guerrero Moreno, Yanina Yomari (2024)
The present Curricular Integration Work entitled: "PROCEDURES MANUAL FOR THE FULFILLMENT OF TAX OBLIGATIONS OF THE HARDWARE STORE SECTOR IN THE CANTON OF MACARÁ, PERIOD 2023," is aimed at disseminating relevant information and providing a practical tool to serve as a guide and assistance in matters related to taxes. This implies not only offering knowledge about the respective fiscal regulations but also providing resources and practical guidance to help individuals or businesses fulfill their tax obligations effectively and accurately. To achieve the general objective, a manual of tax procedures was developed; in which policies, procedures, flowcharts, and declaration formats for Income Tax (IR) and Value Added Tax (VAT), as well as the preparation and submission of Annexes were developed. This will ensure compliance with the tax obligations of each regime existing in this sector, reducing errors and avoiding possible sanctions. This research work was focused on the creation of tax protocols. It began with the elaboration of procedures for various tax declarations, including income tax for natural persons, VAT, simplified transactional annex, and employment relationship annex. Besides, fundamental aspects such as obtaining the RUC and implementing electronic invoicing were addressed, which is mandatory for both the Entrepreneurial Regime and the General Regime; likewise, by developing and applying a survey as a research instrument, the knowledge that the owners have about taxation and compliance with the tax obligations established in the regulations was analyzed in order to avoid fines or penalties by the Tax Administration. It is concluded that the manual of tax procedures represents a fundamental resource to increase efficiency and transparency in fiscal operations, provides clear and detailed guidelines, facilitates the correct execution of tax processes, which also helps to reduce errors; its implementation contributes to the optimization of resources and the strengthening of Ecuador’s tax system by promoting regulatory compliance and proper management of tax obligations.